DETERMINATION OF THE CONTENT OF FLAVONOIDS IN HAWTHORN (Scientific journal of the Fergana State University, 2023)
Determination of flavonoids in yellow hawthorn, common in Uzbekistan. Flavonoids in the sample were determined using liquid chromatography. Dihydroquercetin, quercetin and rutin were found in freshly cut yellow hawthorn. It was found that the amount of flavonoids in dried hawthorn has decreased